ILLITERACY ELIMINATION AS MOBILIZATION POLITICAL CAMPAIGN: PECULIAR FEATURES OF THE CAMPAIGN IN THE NATIONAL REGION IN THE 1920s (AS EXEMPLIFIED IN KHAKASSIA) - Kostyakova J. B.; Artamonova N. Y. (Scientific Journal of Pedagogy and Economics, 2019)
The aim of the study is to analyze the deals with the illiteracy campaign of 1920s-1930s. We used methods of analysis, synthesis and comparison. Referring to the main definitions and characteristics of the social mobilization, the authors consider the illiteracy campaign as mobilization political campaign. The need to use mobilization methods for this campaign was caused by the military communism to be further fixed by the active promotion of the external military threat. Under those conditions the illiteracy campaign pursued, first of all, political aims, such as political education, support of the government and formation of the Soviet citizen identity. The illiteracy elimination combined persuasion and active enforcement that expanded possibilities of involving the Soviet citizens into the educational process. But the mobilization and bureaucratic nature of the illiteracy campaign implementation and the results assessment did not allow to achieve the goals in the 1920s. One of the reasons for the low rates of the illiteracy elimination in Siberia was insufficient understanding of the cultural and political peculiarities of the national regions. The regional research in Khakassia showed that in the 1920s the illiteracy elimination difficulties were associated with the gangsterism, uncertain status of the region, problematic cross-national relations, Khakass writing obstacles and insufficient material and personnel resources. It is concluded that the solution of these issues and the mobilization methods expansion allowed to intensify the illiteracy elimination in the national regions by the end of the 1920s.